ANALISIS KEPUTUSAN PEMBELIAN SAYUR DENGAN MEDIA ONLINE DI NYAYUR.ID KOTA SALATIGA - Desi Pratisia; Bayu Nuswantara (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
The change in the choice of places for people to shop vegetables with online media can be influenced by various things such as the interest/interest of consumers both in terms of attractive products, convincing promotions, ease of transactions and purchasing processes, cheaper prices with quality services provided. Can be a reason for making a purchasing decision. The purpose of this study is to analyze consumer characteristics, analyze the process of purchasing vegetable decisions, and the relationship between marketing mix and service quality with vegetable purchasing decisions at Nyayur. id. The research method used is a quantitative research using non-probability sampling technique with purposive sampling as many as 60 respondents using the Nyayur.id application with the provision that they have shopped at least 2 times. The analytical techniques used are descriptive analysis, validity test, reliability test, and exploratory factor analysis using the KMO-MSA test (Kaiser-Meyer-Olkin of Measure Sampling Adequacy and Bartlett's Test, and rotation. The results of the study show that there are 8 factors formed. The new factors are promotion factors, product factors and decision-making processes, price factors, products and responsiveness, responsiveness and assurance factors, reliability and assurance factors, product factors, reliability factors, and responsiveness factors.